An extracellular siderophore is required to maintain the mutualistic interaction of Epichloë festucae with Lolium perenne. - Linda J Johnson; Albert Koulman; Michael Christensen; Geoffrey A Lane; Karl Fraser; Natasha Forester; Richard D Johnson; Gregory T Bryan; Susanne Rasmussen (PLoS Pathogens)
We have identified from the mutualistic grass endophyte Epichloë festucae a non-ribosomal peptide synthetase gene (sidN) encoding a siderophore synthetase. The enzymatic product of SidN is shown to be a novel extracellular siderophore designated as epichloënin A, related to ferrirubin from the ferrichrome family. Targeted gene disruption of sidN eliminated biosynthesis of epichloënin A in vitro and in planta. During iron-depleted axenic growth, ΔsidN mutants accumulated the pathway intermediate N(5)-trans-anhydromevalonyl-N(5)-hydroxyornithine (trans-AMHO), displayed sensitivity to oxidative stress and showed deficiencies in both polarized hyphal growth and sporulation. Infection of Lolium perenne (perennial ryegrass) with ΔsidN mutants resulted in perturbations of the endophyte-grass symbioses. Deviations from the characteristic tightly regulated synchronous growth of the fungus with its plant partner were observed and infected plants were stunted. Analysis of these plants by light and transmission electron microscopy revealed abnormalities in the distribution and localization of ΔsidN mutant hyphae as well as deformities in hyphal ultrastructure. We hypothesize that lack of epichloënin A alters iron homeostasis of the symbiotum, changing it from mutually beneficial to antagonistic. Iron itself or epichloënin A may serve as an important molecular/cellular signal for controlling fungal growth and hence the symbiotic interaction.